2017
DOI: 10.1051/shsconf/20173300011
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Construction of ‘National Unity’ in Malaysia: Framing Analysis of Texts and Audiences

Abstract: Abstract. This paper examines the construction of 'national unity' within the culturally diverse society of Malaysia. It does so through a framing analysis of 102 recent Malaysian government advertisements. Audience responses, based on a series of focus group interviews, were also analysed. Although the power of visual advertisements comes from its capacity to blend fact and emotion, to engage audiences, and to add the narrative complexity of ethnicities, this paper also discovers a struggle over the meaning w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…As such, the power of language through jingles and slogans created to entrench the positive image of nation branding into the people's mind-set. As for the government billboards, the result is consistent with the finding in a study done by Ahmad Tajuddin et al (2017) where the use of jingles, catchphrases, and slogans, apart from being a persuasive strategy and promotion, is also used to describe the Government's aims and intentions. For instance, the tagline Perkukuhkan Perpaduan Demi Kestabilan Negara (Strengthening unity for the State stability) provides the impression of how nation-building can be achieved through unity of the people (See Figure 1) and through the spirit of patriotism towards the country (See Figure 2) and thus exhibits a 'banalized image of the nation' (Castelló 2009, p. 309).…”
Section: The Language Of Nation-buildingsupporting
confidence: 86%
See 2 more Smart Citations
“…As such, the power of language through jingles and slogans created to entrench the positive image of nation branding into the people's mind-set. As for the government billboards, the result is consistent with the finding in a study done by Ahmad Tajuddin et al (2017) where the use of jingles, catchphrases, and slogans, apart from being a persuasive strategy and promotion, is also used to describe the Government's aims and intentions. For instance, the tagline Perkukuhkan Perpaduan Demi Kestabilan Negara (Strengthening unity for the State stability) provides the impression of how nation-building can be achieved through unity of the people (See Figure 1) and through the spirit of patriotism towards the country (See Figure 2) and thus exhibits a 'banalized image of the nation' (Castelló 2009, p. 309).…”
Section: The Language Of Nation-buildingsupporting
confidence: 86%
“…Past studies have revealed that language, other than used as a tool to exchange communication and information, is a means of nation-building (John 2015;Heng 2017). In this sense, language is viewed as an instrument of cultural integration and assimilation (Noels 2014), and also a vehicle of exposing state ideology (Ahmad Tajuddin et al 2017). Although there are many definitions that reflect the notion of social identity, the one that best fits this paper is to take individual history into account when discussing social reality.…”
Section: Language and Social Identitymentioning
confidence: 97%
See 1 more Smart Citation
“…Studies interested in their understanding of, and alignment with, the campaign objectives of 1Malaysia, for example, report, on the one hand, that citizens show a clear grasp of its conception of unity and agreement on unity as an appropriate political goal for the country (Ismail & Ahmad, 2014). Clearly reflected on the other hand, however, is disagreement among ethnic groups over the ideas of unity expressed in the campaign images (Zeiny & Yusof, 2013), alongside clear alternative definitions of unity, from them, based on their lived experiences (Tajuddin et al, 2017), and even a variety of criticisms of the campaign as state rhetoric (Chinnasamy et al, 2020; Harris & Han, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…When the flag was used as the subject of the advertisement it is interpreted as something beyond the national symbol since it also represents the history of the country, its achievements, its ideals and also its struggles. The use of pictures, photographs, or visual images is not only a tool for constructing 'national unity' and identity; but in a way to show that the State is a legitimate actor in shaping the society (Ahmad Tajuddin et al, 2017;Rietveld, 2013). Looking at the intra-textual interaction of 1Malaysia logo and a statement that is translated as '1Malaysia is the pillar to the prosperity and progress of the people of Malaysia'; it shows how an ideology is expressed and how it is linked to the society through the elements of reasoning devices supporting the advertisements.…”
Section: Exemplars -mentioning
confidence: 99%